Theories and cognitive models of postnonclassical learning in natural science education - Suriya Irekovna Gilmanshina; Lyudmila Vladimirovna Moiseeva; Inna Nikolaevna Pushkareva; Sergey Borisov Ignatov; Iskander Rafailevich Gilmanshin (Revista on line de Política e Gestão Educacional)
Introduction. The cognitive models formed in post – non-classical science-the theory of systems, the theory of self-organization and management, which were developed in natural science, are now widely used in social and humanitarian research. However, they have not yet been properly reflected in the content of natural science education of future employees of these fields – graduates of social, humanitarian and pedagogical departments of higher education institutions. The purpose of this study: theoretical and methodological justification, development and testing of a set of methodological tools for adapting cognitive models of post-non-classical science in the content of natural science education of students of social and humanitarian fields of higher education. Methodology and methods. The methodological basis of the research is based on the ideas of the system-synergetic approach, works on the philosophy and methodology of education, fundamental positions and basic principles of modern didactics. The theoretical basis is the works of domestic and foreign scientists on the development of the content of education, educational technologies and the organization of the educational process at the University. Used – modeling and forecasting, analysis and synthesis, observation, questioning, testing, experimental work. Results and scientific novelty. The theoretical and methodological justification of the need to adapt cognitive models of post-non-classical science in the content of natural science education of the Humanities is given, and the principles are defined. The complex has a linear-concentric structure and includes a basic training course, a system of elective training courses and interdisciplinary modules, technologies and teaching methods that support it. During testing of the complex was performed: ability to operate basic concepts of post-nonclassical science and apply them to describe the behavior of social and natural systems of different complexity, the volume of natural Sciences students ' knowledge, proficiency with the operation of their transfer to other subject areas.